2019
DOI: 10.1021/acsomega.8b02987
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Monodispersed SiO2@Fe3O4 Core–Shell Colloids for Printing and Three-Dimensional Coating with Noniridescent Structural Colors

Abstract: Amorphous photonic structures (APSs) with short-range ordered arrangement have attracted great interest because of their wide view angles. However, the presented methods for the APSs color printing and 3D coating on different substrates and curvatures are lack of control. Here, APSs with angle-independent structural colors were fabricated by the self-assembly of SiO 2 @Fe 3 O 4 core–shell nanostructures, which were prepared by the hydrolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…The structural color and the stop band of photonic crystals can be controlled through altering the lattice constant, refractive index, or the orientations of ordered structures. These unique properties enable PCs to show considerable applications in color display, [ 1–8 ] sensing, [ 9–22 ] printing, [ 23–29 ] anticounterfeiting, [ 30–38 ] photocatalysis, [ 39–41 ] optical device, [ 42–46 ] and solar energy. [ 47–50 ]…”
Section: Introductionmentioning
confidence: 99%
“…The structural color and the stop band of photonic crystals can be controlled through altering the lattice constant, refractive index, or the orientations of ordered structures. These unique properties enable PCs to show considerable applications in color display, [ 1–8 ] sensing, [ 9–22 ] printing, [ 23–29 ] anticounterfeiting, [ 30–38 ] photocatalysis, [ 39–41 ] optical device, [ 42–46 ] and solar energy. [ 47–50 ]…”
Section: Introductionmentioning
confidence: 99%
“…A similar enhancement of structural colours by adding a black-coloured component was reported in systems based on artificial colloidal crystals as well as in nature. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Most of those studies employed black-coloured coating [22][23][24][25][26][27][28] or used a black material as the background. 13 A previous study suggested that the black materials improve the saturation of structural colours by absorbing scattered light in a broad wavelength range.…”
Section: Doping Of Black Carbon Nanoparticles Into Colloidal Crystals Of Silica Nanoparticlesmentioning
confidence: 99%
“…Some researchers tried to enhance the contrast of structural colours by adding black-coloured materials. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] For instance, adding a small amount of carbon black powder to a colloidal crystal of polystyrene nanoparticles reduced the incoherent scattering considerably. [16][17][18][19][20][21][22] A black coating on the nanoparticles could also increase the saturation of structural colours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By introducing responsive building blocks, polymers, or other components into the colloidal photonic crystals, responsive photonic crystals can be prepared and their color can be changed depending on the physical or chemical stimulations . These photonic crystals with brilliant structural colors have attracted considerable interests due to their growing applications in the field of reflection mode‐based color display, sensor, printing, anti‐counterfeiting, optical device, photocatalysis, and solar cell …”
Section: Introductionmentioning
confidence: 99%